Evaluation of minimum capital requirements for bank loans to SMEs - Klaus Düllmann; Philipp Koziol (Deutsche Bundesbank, 2013)
Our paper addresses firm size as a driver of systematic credit risk in loans to small and medium enterprises (SMEs). Key contributions are the use of a unique data set of SME lending by over 400 German banks and relating systematic risk to the size dependence of regulatory capital requirements. What sets our sample apart is its comprehensive coverage of the particularly rich and well developed credit market for SMEs in Germany. We estimate asset correlations as the key measure of systematic risk from historical default rates. Our results suggest that systematic risk tends to increase with firm size, conditional on the respective rating category. We also compare the size of this effect with the capital relief that has been granted in Basel II for SMEs relative to large firms. For SME loans in the corporate portfolio of the Internal Ratings-Based Approach and also for SME loans treated under the revised standardized approach of Basel II, our asset correlation estimates suggest a significantly larger relative difference from large firms than reflected in the regulatory capital requirements.
Keywords: G21; G33; C13; 330; Asset Correlation; Basel II; Minimum Capital Requirements; Single Risk Factor Model